Interest rate shocks, competition and bank liquidity creation - Kick, Thomas (Financial Markets and Portfolio Management, 2022)
We study the effects of interest rate shocks (IRS) on banks’ liquidity creation. A unique supervisory data set from the Deutsche Bundesbank allows identifying banks’ liquidity creation for the real economy and the effects of banking market competition. Here, we employ a novel approach to account for IRS that are both unexpected and effective for a bank’s business model. We find that higher individual pricing power in the market lowers banks’ liquidity creation, which is in line with theory that monopolistic firms undersupply the market when utilizing their high pricing power in the bank competition–liquidity creation nexus. While positive IRS per se lead to an increase in bank liquidity creation, we find that a high bank-individual pricing power curbs this impact on liquidity creation significantly. Moreover, we show that monetary policy was most effective during the global financial crisis and for well-capitalized banks, whereas periods of low interest rates are characterized by the persistent increase in liability-side liquidity creation.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Bank liquidity creation; Banking market competition; Dynamic GMM; Financial crisis; Financial markets regulation; Low interest rate environment; Unexpected monetary policy